Perceived stress from social isolation or loneliness among clinical and non-clinical healthcare workers during COVID-19 - Katherine A. Meese; Laurence M. Boitet; Katherine L. Sweeney; David A. Rogers (BMC, 2024)
Abstract Background Workplace social isolation and loneliness have been found to result in a decline in job satisfaction and an increase in burnout among working individuals. The COVID-19 pandemic exacerbated feelings of loneliness and social isolation among healthcare workers. The majority of research on healthcare worker experiences is conducted in siloes which does not reflect the shared experiences of interprofessional teams. The purpose of this study is to understand stress from social isolation or loneliness across the entire clinical and non-clinical healthcare team over the course of the pandemic. Methods Data was acquired using a cross-sectional survey distributed to healthcare workers once a year at a large academic medical center in the Southeastern United States during the COVID-19 pandemic (2020-2022). Information pertaining to job role, work location, and demographic factors was collected. Participants were also asked to assess individual well-being and resilience, in addition to reporting stress derived from various sources including job demands and social isolation or loneliness. Descriptive statistics and bivariate analyses were conducted to assess the association between stress from social isolation or loneliness and individual characteristics. Results Stress from social isolation or loneliness was found to decrease over the survey period across all measured variables. Trainees and physician-scientists were found to report the highest rates of this stressor compared to other job roles, while Hospital-Based ICU and Non-ICU work locations reported the highest rates of loneliness and social isolation stress. Younger workers and individuals from marginalized gender and racial groups were at greater risk for stress from social isolation or loneliness. Conclusions Given the importance of social connections for well-being and job performance, organizations have a responsibility to create conditions and mechanisms to foster social connections. This includes establishing and reinforcing norms of behavior, and developing connection mechanisms, particularly for groups at high risk of loneliness and social isolation.